The relationship between Corporate Social responsibility to the Brand Image and Brand Loyalty of Green Leaf Hotel Group - Supornrungcharoen, Janjao; Laohavichien, Tipparat (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2021)
The objectives of this study are to investigate a level of respondents’ opinions on corporate social responsibility, brand image, and brand loyalty, and examine the relationship between corporate social responsibility and brand image, the relationship between corporate social responsibility and brand royalty, and the relationship between brand image and brand loyalty. By using survey data collected from customers of hotels in the Green Leaf Hotel Group and analyzing them through the Independent Sample t-test, one-way ANOVA (F-test), Regression Analysis, Pearson’s Correlation Coefficient, and Spearman rank, the findings reveal that while gender, status, and education level have no effect on the respondents’ opinions, age (specifically, between 26-33 years) and monthly income (specifically, between 25,001-35,000 Baht) do have effect on individual opinions on corporate social responsibility of the hotels in the Green Leaf Hotel Group. Lastly, this study finds that corporate social responsibility is positively associated with brand image and with brand loyalty as well as brand image is positively associated with brand loyalty.